In-situ investigation on the oxygen vacancy-driven topotactic phase transition in charge-orbital ordered Nd0.5Sr0.5MnO3 films. (15th February 2023) - Xiao, Andong; Liu, Yao; Yang, Tianzi; Jia, Wentao; Song, Xin; Qian, Yu; Liang, Chenyu; Ma, Tianyu
Abstract: The topotactic phase transition from perovskite to oxygen vacancies ordered brownmillerite structure in transition metal oxides intrigues various new application possibilities. However, the in-situ observation of the oxygen vacancies formation process accompanying the phase transition is still rare. Here in this article, we report the topotactic phase transition from the perovskite to a brownmillerite phase transition in the intermediate bandwidth- (101)-Nd0.5 Sr0.5 MnO3- δ films. The oxygen vacancies migration process in the films was identified by the TEM technique during the in-situ high vacuum annealing process. The TEM results demonstrate a vertical brownmillerite structure with the oxygen vacancies channel perpendicular to the film plane in the (101)-oriented films. Moreover, the in-situ investigation reveals that oxygen atoms in the {010}PV plane of the perovskite phase migrate out of the film along the out-of-plane <101>PV direction at first, and the formed oxygen vacancies become ordered by elongating the high-vacuum annealing process to 42 h, transforming to the brownmillerite structure. Further studies reveal that the associated physical properties of the topotactic phases can be controlled by the phase transition. The charge-orbital ordered antiferromagnetic insulating ground state transfers to a highly insulating state with a novel magnetic phase that is distinct from that of brownmillerite structure of other manganites. The present studies thus pioneered topotactic phase transition in a new manganite system and provide useful information for developing perovskite-based functional materials by defect engineering. Graphical abstract: Image, graphical abstract